An Analysis of Students Learning Styles in Listening Comprehension - welly wandini; Maliqul Hafis; Sahrawi Syahrawi; Dayat Dayat (Journal of English Language Teaching and Education (JELTE), 2024)
ABSTRACTThis research aims to find out the learning styles of students and the level of listening comprehension according to the students learning styles.  In this research, researcher used direct and indirect communication techniques. The population for this thesis was third semester students of English Education Study Program, IKIP PGRI Pontianak, and then twenty-five students at IKIP PGRI Pontianak were involved in this thesis. The researcher used questionnaires to collect quantitative data, and interviews to collect qualitative data. To analyze the data, from the questionnaire, researcher classify based on the students learning styles and present it in percentage form. from the interview, researcher find out the level of listening comprehension based on the students  learning style and then analyze it using thematic analysis. Based on the results of research through questionnaires, researcher found the percentage of learning styles possessed by IKIP PGRI Pontianak students. Visual learning style students (36%), aural/auditory learning style (20%), kinesthetic learning style (44%). Through interviews, Researcher found listening comprehension levels based on three learning styles: visual, aural/auditory, and kinesthetic.Keywords: Learning Styles, Listening Comprehension, Descriptive Study